Experimental study on the recovery of sodium in high sodium fly ash from thermochemical conversion of Zhundong coal. (1st October 2018) - Yang, Shaobo; Song, Guoliang; Na, Yongjie; Qi, Xiaobin; Yang, Zhao
Highlights: Zhundong coal gasification/combustion fly ash is rich in Na resources. Most of the Na in Zhundong coal fly ash can be effectively removed by water washing. The recovery products of Na are mainly composed of NaCl and Na2 SO4. It is more suitable for recovering Na from fly ashes of Shaerhu and Tianchi coals. The recovery of Na from Zhundong coal fly ash is feasible in technology and economy. Abstract: Zhundong (ZD) coal gasification/combustion fly ash is a high Na content residual product and contains a large quantity of harmful elements, including as Cl, S, and Na that must be removed and recovered. Water-soluble Na is the predominant Na form in ZD coal fly ash, accounting for 34.7–92.8% of the total Na. The main minerals of Na identified were NaCl and Na2 SO4 . Most of the water-soluble Na in the ZD coal fly ash can be effectively removed by water washing, the removal yields have been found to be 31–93%. Increasing the washing time, water temperature, liquid–solid ratio and acid concentration can increase the Na removal yield. For the ZD coal combustion fly ash (SEHcf) and gasification fly ash (SEHf), NaCl particles are present on the fly ash surface, most water-soluble Na was washed by water in 5 min at 30 °C. However, the removal of Na by water washing was inhibited by the water insoluble calcium oxides and sulfides that covered the surface of the ZD coal gasification fly ashes (TCf and SHf), Na removal required higher wash water temperatures and longer washing times. It is feasible to recover Na from ZD coal fly ash by water washing, and the recovered Na products are primarily NaCl and Na2 SO4 . The recovery yields of Na in the SEHcf, SEHf and TCf were 49.4%, 81.2%, and 65.4%. But the recovery yield of Na in SHf was 16.6%. SEHcf, SEHf and TCf were more suitable for recovering Na. the recovery of Na from ZD coal fly ash is economically feasible.